Cement and claydite dust binding compositions - D. S. Makhortov; L. Kh. Zagorodnyuk; N. A. Shapovalov; D. A. Sumskoy (Вестник СибАДИ)
Introduction. The article presents the production results for binder compositions of the optimal proportion based on Portland cement and claydite waste – claydite dust. The granulometric composition studies have been conducted, test results for binder compositions of different proportions are presented: cement – claydite dust, jointly mechanically activated in a vibrating mill. The binder compositions with a wide range of use have been developed and determined. Using the electron microscopy method, microphotographs of cement stones chips made from Portland cement and different contents of claydite dust, which have been mechanically activated in a vibrating mill, were taken. There is active overgrowth of open pores in cement stones obtained from binder compositions by neoplasms of various sizes.After the use of claydite dust as a raw mix, the structure of the composite is compacted.Materials and methods. ЦЕМ0 52.5N Portland cement (GOST 31108-2020) produced by ZAO Belgorodskii Cement and claydite dust, the waste of claydite dust production, were used in the work. The mechanical activation was performed by grinding in a vibrating mill. The normal density was determined using the Vic’s device according to GOST. The granulometric composition was studied using the AnalyssetteNanoTecplus device. The microstructure was studied using a high-resolution scanning electronic TESCAN MIRA 3 LMU microscope. In order to construct diffractograms, the ARL X’TRA Thermo Fisher Scientific device was used.Results. The binding composition of the optimal proportion of claydite dust demonstrates an increase in strength characteristics, there is a compaction of the cement stone structure compared to ordinary Portland cement.Discussion and conclusions. The use of waste from the production of claydite – claydite dust as a mineral filler of the binder composition makes it possible to save expensive Portland cement, while increasing the strength characteristics of the binder composition.